The Ablation System. More favorable contravention law or legal facility? Brief considerations on Law no. 155/2020: Array - Zorzoana , Alina (Acta Universitatis Danubius. Juridica, 2021)
This article aims to be a comparative analysis between the concepts of more favourable contravention law and legal facility, regarding the ablation system provided by Government Ordinance no. 2/2001 on the legal regime of contraventions, with subsequent amendments and supplementations. Thus, we shall try to answer the question what is the legal nature of the ablation system? The discussions are in both directions, as there are opinions according to which the ablation system corresponds to the material law, when it actually is a more favourable legal regulation. Obviously the effects of the two institutions are different and we shall analyze them herein below. We chose as a case study Law no. 155/2020 for amending and supplementing the Law on electricity and natural gas no. 123/2012 and on amending and supplementing other regulations, which exempted the ablation system in the field of electricity from application.